Concatenated and interleaving codes for MC DS CDMA using Cadence virtuoso. (2016) - Saravanakumar, S.; Deepa, R.
Multi carrier DS CDMA technique is the next generation mobile communication system for future advances. Error correcting codes and concatenated codes are used for correcting the errors in data transmission. In this paper, hybrid concatenated codes for MC DS CDMA structure has been proposed and parameters like usage time, power consumption and area are estimated. Further system performance can be attained by serially concatenating the proposed scheme with outer and inner codes. The interleavers are used for concatenated codes and it reduces the burst errors between outer and inner code of encoding and decoding operation in the MC DS CDMA model. In this paper, Verilog code is used for designing the entire structure of CDMA model. The simulation and estimated parameters is done by Cadence design environment.